The cross‐entropy method for combinatorial optimization problems of seaport logistics terminal - Yildiz, Turkay; Yercan, Funda (Transport, 2010)
Studies on seaport operations emphasize the fact that the numbers of resources utilized at seaport terminals add a multitude of complexities to dynamic optimization problems. In such dynamic environments, there has been a need for solving each complex operational problem to increase service efficiency and to improve seaport competitiveness. This paper states the key problems of seaport logistics and proposes an innovative cross‐entropy (CE) algorithm for solving the complex problems of combinatorial seaport logistics. Computational results exhibit that the CE algorithm is an efficient, convenient and applicable stochastic method for solving the optimization problems of seaport logistics operations.First published online: 10 Feb 2010